Transforming agricultural support for a sustainable future: A Latin America and Caribbean view - Laborde Debucquet, David; Olivetti, Elsa B.; Piñeiro, Valeria (International Food Policy Research Institute, 2024)
Addressing the complex challenges facing agricultural and food systems requires a detailed and integrated approach that ensures food security, enhances nutrition, protects environmental sustainability, and supports livelihoods. Governments are crucial in guiding this transformation through a range of policy tools, including regulatory measures, market-based mechanisms, price adjustments that reflect true production costs, and the reassessment of agricultural subsidies. Achieving comprehensive solutions to these challenges across the domains of food security, nutrition, and sustainable development hinges on reforming domestic agricultural support.